Pengaruh Gaya Kepemimpinan dan Produktivitas Kerja terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Depok - Faizatunnisa Faizatunnisa; Syahrial Addin; Yulia Mujiaty (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of leadership style and work productivity on employee performance both partially and simultaneously. This study uses a quantitative approach with a saturated sampling method on the entire population of DPMPTSP employees totaling 59 respondents. Data were collected through questionnaires and analyzed using multiple linear regression and validity, reliability, T-test, F-test, and coefficient of determination tests with the help of SPSS software version 21. The results of the t-test that leadership style (X1) has a significant effect on work performance, can be seen from the calculated t value of 3.365> t table 2.003 and a significance value of 0.001 <0.05, Work productivity (X2) has a significant effect on performance obtained a calculated t value of 2.333> t table 2.003 and a significance value of 0.023 <0.05. The f test obtained a calculated f value of 30.680 > f table 3.16 and a significance value of 0.000 < 0.05, so it can be concluded simultaneously that leadership style and work productivity have a significant effect on employee performance. Leadership style contributes an influence of 47.6%, work productivity of 42.6%, and both simultaneously explain 52.3% of employee performance variables. These findings provide strategic recommendations for government agencies to improve employee performance through strengthening leadership and increasing work productivity.